Spatial Attentional Selection Modulates Early Visual Stimulus Processing Independently of Visual Alpha Modulations - Gundlach, C; Moratti, S; Forschack, N; Müller, M M (Cerebral cortex (New York, N.Y. 1991), 2020)
The capacity-limited human brain is constantly confronted with a huge amount of sensory information. Selective attention is needed for biasing neural processing towards relevant information and consequently allows meaningful interaction with the environment. Activity in the alpha-band has been proposed to be related to top-down modulation of neural inhibition and could thus represent a viable candidate to control the priority of stimulus processing. It is, however, unknown whether modulations in the alpha-band directly relate to changes in the sensory gain control of the early visual cortex. Here, we used a spatial cueing paradigm while simultaneously measuring ongoing alpha-band oscillations and steady-state visual evoked potentials (SSVEPs) as a marker of continuous early sensory processing in the human visual cortex. Thereby, the effects of spatial attention for both of these signals and their potential interactions were assessed. As expected, spatial attention modulated both alpha-band and SSVEP responses. However, their modulations were independent of each other and the corresponding activity profiles differed across task demands. Thus, our results challenge the view that modulations of alpha-band activity represent a mechanism that directly alters or controls sensory gain. The potential role of alpha-band oscillations beyond sensory processing will be discussed in light of the present results.